Development of Minimum Competency Assessment (AKM)-Based Exercise Books to Improve Students' Literacy and Numeracy Skills at Sdn Janti 02 Sidoarjo - Nuril Nuzulia; Abd Gafur (Universitas Muhammadiyah Sidoarjo, 2022)
Develop a Minimum Competency Assessment-Based Exercise Book to Improve Students' Literacy and Numerical Ability at SDN Janti 02 Sidoarjo to provide exciting and creative learning media in a lesson that aims to improve student learning outcomes. This is one of the reasons behind this development research. The study aimed to develop a minimum competency assessment-based exercise book to enhance students' literacy and numeracy skills at SDN Janti 02 Sidoarjo. This research and development method uses the research and development (R&D) type of Borg & Gall. The results of the development were in the form of a